2007
DOI: 10.1002/ppul.20574
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine induction by respiratory syncytial virus and adenovirus in bronchial epithelial cells

Abstract: In order to broaden our knowledge of the primary immune responses to respiratory syncytial virus (RSV) and adenovirus infections, we compared the concentrations of interleukin (IL)-6, IL-8, and regulated on activation, normal T cell expressed and secreted (RANTES) produced in vitro during RSV and adenovirus infections of bronchial epithelial cells. We infected BEAS-2B cells-a human bronchial epithelial cell line-with RSV, adenovirus serotype 3, or serotype 7 and measured the concentrations of IL-6, IL-8, and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 13 publications
5
30
1
Order By: Relevance
“…The airway epithelial inflammatory response towards respiratory viruses is of considerable variability and depends, among other factors, on virus type, strain and load, cell culture conditions and infected cell type [32][33][34]. Thus, data obtained from only a single in vitro model system should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…The airway epithelial inflammatory response towards respiratory viruses is of considerable variability and depends, among other factors, on virus type, strain and load, cell culture conditions and infected cell type [32][33][34]. Thus, data obtained from only a single in vitro model system should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Endotoxin, or its purified derivative LPS, a cell wall component of Gramnegative bacteria, is a potent proinflammatory constituent continuously shedding into the environment, which is important in the pathogenesis of airway inflammatory diseases such as asthma. To study whether LPS-induced cytokine or chemokine production in noninfected airway epithelial cells, we chose chemokine CXC family member IL-8, IL-6 cytokine and the chemokine CCL family member RANTES as examples, as they also play a pivotal role in airway immune response to RSV infection (15,19). We found that incubation with 50 g/mL LPS (the dose choosing data were not shown) slightly up-regulated IL-6 production in 9HTEo cells (Fig.…”
Section: Tlrs Expression Pattern In 9hteo Cellmentioning
confidence: 98%
“…IL-8 primarily targets the neutrophil and promotes neutrophil migration to the site of inflammation. It is suggested that neutrophils induced by IL-8 inflammation play an important role during airway RSV infection (37). RANTES and IL-8 induced by RSV infection activate the release of leukotrienes and histamine in primed mast cells and basophils (2,4).…”
Section: Discussionmentioning
confidence: 99%